2006
DOI: 10.2353/ajpath.2006.060073
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nicotinamide Adenine Dinucleotide Phosphate Oxidase-Derived Reactive Oxygen Species in the Acquisition of Metastatic Ability of Tumor Cells

Abstract: We examined the role of phagocyte-derived oxygen radicals in tumor cell acquisition of metastatic phenotype by comparing gp91(phox-/-) mice and C57BL/6J wild-type (WT) mice. The gp91(phox-/-) mouse is deficient in the gp91(phox) gene, an essential subunit of the phagocyte nicotinamide adenine dinucleotide phosphate oxidase that generates superoxide anion. QR-32 fibrosarcoma cells are nonmetastatic but are converted into metastatic tumors once in contact with foreign body (gelatin sponge)-induced phagocytes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…In contrast, the phagocytes obtained from knockout mice did not have such activity. 98 Moreover, administration of aminoguanidine, a broad inhibitor for inducible nitric oxide synthase, partially but significantly suppressed malignant conversion in the model 93 ; thus we concluded that RNS were also involved in the process. These results show that ROS and RNS, derived from foreign-body-induced neutrophils, are an intrinsic factor in the conversion of regressive tumors to more malignant ones.…”
Section: Experimental Models Of Foreign-body-induced Carcinogenesis Amentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast, the phagocytes obtained from knockout mice did not have such activity. 98 Moreover, administration of aminoguanidine, a broad inhibitor for inducible nitric oxide synthase, partially but significantly suppressed malignant conversion in the model 93 ; thus we concluded that RNS were also involved in the process. These results show that ROS and RNS, derived from foreign-body-induced neutrophils, are an intrinsic factor in the conversion of regressive tumors to more malignant ones.…”
Section: Experimental Models Of Foreign-body-induced Carcinogenesis Amentioning
confidence: 69%
“…Moreover, acquisition of metastatic ability was reduced in the mice. 98 Thymosin ß4, a genetic marker of QR cell progression, 91 was not detected in the arising tumors in gp91 phox2/2 mice. To confirm whether phagocyte-derived ROS were actually involved in tumor progression, we isolated phagocytes from wild-type mice and transferred them into gp91 phox2/2 mice.…”
Section: Experimental Models Of Foreign-body-induced Carcinogenesis Amentioning
confidence: 95%
“…We have previously revealed that the survived cell population from benign QR-32 cells was converted into aggressive tumor cells by inflammatory cell-derived ROS-and NOmediated injury. 29,30 The QR-32 cells used in the study are a typically sensitive clone to ROS injury because they contain less antioxidative enzymes (low in manganese superoxide dismutase and glutathione peroxidase activities), compared with ROS-resistant clones. 28 Therefore, we assumed that ROS-affected surviving cells would be prone to convert themselves into more malignant ones.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed methods for isolating peritoneal exudate cells from mice were described in a previous report. 29 …”
Section: Detection Of Nitric Oxide In the Culture Supernatantsmentioning
confidence: 99%
See 1 more Smart Citation